"Coming out" as an alcoholic: how former problem drinkers negotiate disclosure of their nondrinking identity. Issue 3 (3rd March 2016) - Romo, Lynsey K.; Dinsmore, Dana R.; Watterson, Tara C.
Abstract: Although communication is critical for former problem drinkers to reject drinks, socialize with others, minimize stigma, and maintain their health and sobriety, recovering alcoholics' communication has not been examined beyond alcohol self-help groups. Using a Communication Privacy Management framework and in-depth, semistructured interviews, this study examined how former problem drinkers negotiate the disclosure of their nondrinking status. As participants perceived not drinking in the United States as deviant and socially risky, the investigation found participants primarily concealed their nondrinking status in order to fit in. Participants enacted specific communicative behaviors to regulate their privacy boundaries, only disclosing their struggles with alcohol when benefits outweighed costs (e.g., inspiring others, maintaining sobriety, or building relationships). This study offers practical disclosure strategies for former problem drinkers to protect their private information, manage social interactions, and stay sober.